The Influence of Efficiency and Effectiveness in the Utilization of School Operational Assistance Funds on the Quality of Teaching and Learning Services: A Case Study at SMP Negeri 12 Mimika and SMP Negeri Naena Muktipura - Fitri Dyan Agustin; Mesak Iek; Yundy Hafizriandra (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Sekolah Tinggi Ilmu Ekonomi Krakatau, 2025)
Purpose: This study examines how efficiency and effectiveness in using BOS funds influence the quality of teaching and learning at two junior high schools in Papua—SMPN 12 Mimika and SMPN Naena Muktipura. Methodology/approach: A mixed-method approach was used, combining surveys, interviews, observations, and document analysis. Quantitative data were analyzed with multiple linear regression, while qualitative insights were examined through content analysis. Results/findings: Efficiency (B = 0.670) and effectiveness (B = 0.553) significantly improve service quality. SMPN 12 Mimika performed better overall in fund use, facilities, and teacher training. Conclusions: Efficient and effective use of BOS funds significantly improves teaching and learning quality. Efficient fund management has a stronger effect, especially in enhancing facilities and teacher training, highlighting the need for transparent and well-targeted BOS fund utilization. Limitations: Limited to two schools in Papua, reducing generalizability. Broader studies are needed. Contribution: Provides empirical evidence for improving BOS fund use and educational policy in under-resourced schools.